2013
DOI: 10.1259/dmfr.20130022
|View full text |Cite
|
Sign up to set email alerts
|

Topical contrast agents to improve soft-tissue contrast in the upper airway using cone beam CT: a pilot study

Abstract: The purpose of this study is to explore the topical use of radiographic contrast agents to enhance soft-tissue contrast on cone beam CT (CBCT) images. Different barium sulphate concentrations were first tested using an airway phantom. Different methods of barium sulphate application (nasal drops, syringe, spray and sinus wash) were then tested on four volunteers, and nebulized iodine was tested in one volunteer. CBCT images were performed and then assessed subjectively by two examiners for contrast agent unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…There is much debate over the validity of CT and CBCT volumetric analysis in the measurement of function airway spaces. Topical contrast agents have been suggested to improve accuracy in defining soft tissue surfaces (73), an alternative that was not used in any of the included studies. Only a few studies that use CBCT for airway volume calculation describe using any form of standardization of patient positioning and protocol during image capture.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…There is much debate over the validity of CT and CBCT volumetric analysis in the measurement of function airway spaces. Topical contrast agents have been suggested to improve accuracy in defining soft tissue surfaces (73), an alternative that was not used in any of the included studies. Only a few studies that use CBCT for airway volume calculation describe using any form of standardization of patient positioning and protocol during image capture.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The use of contrast agents in DVT examinations to improve soft tissue contrast is still experimental [ 27 ]. Alsufyani et al showed that the mucosal surface of the paranasal sinuses is best opacified by using 25% barium sulfate, while iodine-containing contrast agents are not suitable [ 28 ]. However, even with this approach, the authors failed to reliably opacify soft tissues cranial to the middle turbinate [ 28 ].…”
Section: Digital Volume Tomography (Dvt)mentioning
confidence: 99%
“…Abb 28. MRT einer 66-jährigen Patientin mit einem Karzinom der Nase und Übergreifen des Tumors auf den Nasenrachen.…”
unclassified